Phenotypic characterization of indigenous Cyprus Native Hair Goat breed using quantitative and qualitative trait analysis - Dilek Arsoy; Ibrahima Mahamane Abdourhamane; Mehmet İsfendiyaroğlu (Revista Científica, 2024)
The loss of genetic diversity in farm animal genetic resources is a growing concern, with many local breeds facing possible extinction. This study on Goat production in Cyprus was carried out to establish the morpho–biometric profile of indigenous Cyprus Native Hair Goats, for which there is no scientific information necessary for their proper classification and identification, for that purpose 60 animals were measured on 17 morphobiometric traits. A two–way analysis of variance with the interaction of the effects of age and gender was performed. White, chamoise, light buckskin, brown–white, white–grey, grey, pinto, and bay colors were the common coat colors recorded with proportions of 28.6; 14.29; 14.29; 14.29; 7.14; 7.14; 7.14 and 7.14%, respectively. All the Cyprus Hair Goats had horns with an arc shape. Wattles, beard, topknot, and feathered feet traits were seen in proportions of 14.3, 57.14, 50 and 21.43%, respectively. Gender factor showed a significant (P<0.05) effect on ear length, head length, wither height, heart girth, chest width, body length, hip height, cannon circumference, and body weight, as well as on morphological indices such as foreleg length, compact index, and area index. However, female Cyprus Hair Goats recorded greater proportionality index values than males. This revealed that females had a brevilinear profile with dairy–type breed characteristics and males were mesolinear with a meat–type profile. Further studies are needed to highlight and expose the potential genetic material of Cyprus Native Hair Goats.